Moral and Ethical Education for Students at the University of Quality Medan - Sinabutar, Octavia; Munthe, Hadriana Marhaeni; Siregar, Robert Tua; Ismail, Rizabuana; Sitorus, Henry (Technium Social Sciences Journal, 2023)
Moral and ethical education is one of the keys to the progress of the Indonesian nation through young people who have good morals and ethics. The purpose of this study was to find out how the role of dormitory administrators socialize Moral and Ethical Education to female students who live in the Girls Dormitory of Quality University Medan. The analytical method uses qualitative research methods with triangulation data collection techniques. The results of this study indicate that dormitory administrators consistently socialize moral and ethical education through training with various sets of dormitory rules and regulations, examples of good behavior, advice, motivation, and self-development of female students. The habit of living in the girls’ dormitory at Quality Medan University makes female students accustomed to living with discipline, honesty, responsibility, wisdom, mutual respect, confidence, having a good mentality, and being able to lead and always have sound life principles. They can form a young generation that is disciplined, has reasonable responsibilities, and is ready to face increasingly advanced times. Future research is important to see the differences in moral and ethical behavior of female students who live in dormitories and those who do not live in dormitories.